Reconstitution of a Staphylococcal Plasmid-Protein Relaxation Complex In Vitro - Caryl, Jamie A. (American Society for Microbiology, 2004)
The isolation of plasmid-protein relaxation complexes from bacteria is indicative of the plasmid nicking-closing equilibrium in vivo that serves to ready the plasmids for conjugal transfer. In pC221 and pC223, the components required for in vivo site- and strand-specific nicking at oriT are MobC and MobA. In order to investigate the minimal requirements for nicking in the absence of host-encoded factors, the reactions were reconstituted in vitro. Purified MobA and MobC, in the presence of Mg(2+) or Mn(2+), were found to nick at oriT with a concomitant phosphorylation-resistant modification at the 5′ end of nic. The position of nic is consistent with that determined in vivo. MobA, MobC, and Mg(2+) or Mn(2+) therefore represent the minimal requirements for nicking activity. Cross-complementation analyses showed that the MobC proteins possess binding specificity for oriT DNA of either plasmid and are able to complement each other in the nicking reaction. Conversely, nicking by the MobA proteins is plasmid specific. This suggests the MobA proteins may encode the nicking specificity determinant.